ANALISIS SEMIOTIKA KATA IBIL DALAM AL-QUR'AN PERSPEKTIF CHARLES SANDERS PEIRCE - Wahyu Fitria; Misnawati (Sekolah Tinggi Ilmu Al-Quran dan Sains Al-Ishlah, 2025)
Interpretations of the word ibil in surah al-Ghashiyah verse 17 generally been literal, focusing primarily on biological and ecological aspects. However, from a semiotic perspective, the term holds deeper symbolic meanings. This study aims to explore the meaning of ibil through the semiotic framework of Charles Sanders Peirce by examining the triadic relationship between sign, object, and interpretant. The method used is a library research approach with qualitative descriptive analysis. The findings reveal that ibil functions as a Representamen that refers to the Object surah al-Ghashiyah verse 17 resulting in three levels of Interpretant: first, ibil is interpreted as a camel in its physical form; second, as a symbol of a large, hump-backed creature; and third, as a symbol of human awareness of God's greatness and power in creating extraordinary beings. These findings demonstrate that a semiotic approach can uncover symbolic meanings within the Al-Qur’an and open up broader and deeper interpretive possibilities regarding the divine messages embedded in the text.